Network value and optimum analysis on the mode of networked marketing in TV media - Xiao Dongpo; Zhenji Zhang; Xiaolan Guan (Journal of Industrial Engineering and Management (JIEM), 2012)
Purpose: With the development of the networked marketing in TV media, it is important to do the research on network value and optimum analysis in this field. Design/methodology/approach: According to the research on the mode of networked marketing in TV media and Correlation theory, the essence of media marketing is creating, spreading and transferring values. The Participants of marketing value activities are in network, and value activities proceed in networked form. Network capability is important to TV media marketing activities. Findings: This article raises the direction of research of analysis and optimization about network based on the mode of networked marketing in TV media by studying TV media marketing Development Mechanism , network analysis and network value structure.
Keywords: 650; TV media Networked Marketing network analysis; the network value and optimization